Service Employment and Unemployment in the Great Recession: Trends in OECD Countries - William Beyers (European Regional Science Association (ERSA), 2010)
Unemployment in Europe has reached 10% as this was prepared, and it is over 10% in the United States at the same time. How has the service economy been related to the current global recession? That is the focus of this paper. Much has been written about the impact of the structural shift to service industries on cyclical fluctuations in advanced economies. In general it has been argued that because the demand for services is relatively steady, a more service-oriented economy should have less cyclicality in employment through business cycles. However, this argument has been made primarily for services sold to consumers, as opposed to services sold on intermediate account (producer services). One of the goals of the current paper is to extend conceptualization of cyclical services demand to producer services, and to evaluate differences in cyclicality and producer and consumer services. The Great Recession that may be benchmarked against December 2007 was strongly associated with troubles emanating from components of the service economy, especially with the finance sector and the financing of housing investment. This paper explores arguments regarding the presumed steadier trajectories for employment in service dominated economies with evidence regarding actual sectoral employment change through the Great Recession. The paper uses data for many OECD countries to evaluate these structural relationships.
Keywords: 330